Penguatan Branding dan Digital Marketing UMKM Keripik Tempe Chatenori - Rahma Gustina; M Habbib Dwi Putra H; Fironika Khoirun niswa; Genta Puja Kusuma; Miko Polindi (LPPI UMN AL WASHLIYAH, 2026)
Micro, Small, and Medium Enterprises (UMKM) make a significant contribution to Indonesia’s economy; however, they still face various challenges, particularly in branding and digital marketing. This study aims to examine the implementation of branding enhancement and digital marketing strategies to improve the competitiveness of the Keripik Tempe Chatenori UMKM. The method used is a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The results show that prior to the assistance program, the UMKM lacked an adequate visual identity and still relied on conventional marketing methods. Branding enhancement was implemented through logo creation, improved packaging quality, and the addition of product labels. Meanwhile, digital marketing was applied by utilizing social media and various digital platforms as promotional tools. This program had a positive impact, including increased product attractiveness, expanded market reach, and improved interaction with consumers. However, challenges remain, particularly in maintaining consistency in managing digital content. Therefore, continuous assistance is needed so that UMKM can optimize their digital strategies more effectively.